Controlled-release of tetracycline and lovastatin by poly(D,L-lactide-co-glycolide acid)-chitosan nanoparticles enhances periodontal regeneration in dogs - Lee BS (Dove Medical Press, 2016)
Bor-Shiunn Lee,1 Chien-Chen Lee,2 Yi-Ping Wang,2 Hsiao-Jan Chen,3 Chern-Hsiung Lai,4 Wan-Ling Hsieh,1 Yi-Wen Chen2 1Graduate Institute of Oral Biology, 2Graduate Institute of Clinical Dentistry, School of Dentistry, National Taiwan University and National Taiwan University Hospital, 3Department of Clinical Laboratory Sciences and Medical Biotechnology, College of Medicine, National Taiwan University, Taipei, 4College of Life Science, Kaohsiung Medical University, Kaohsiung, Taiwan Abstract: Chronic periodontitis is characterized by inflammation of periodontal tissues, leading to bone resorption and tooth loss. The goal of treatment is to regenerate periodontal tissues including bone and cementum lost as a consequence of disease. The local delivery of tetracycline was proven to be effective in controlling localized periodontal infection without apparent side effects. Previous studies suggested that lovastatin has a significant role in new bone formation; however, the local delivery of lovastatin might enhance its therapeutic effects. A number of local delivery devices have been developed recently, including poly(D,L-lactide-co-glycolide acid) (PLGA) nanoparticles. The aim of this study was to develop a local delivery device, PLGA-lovastatin-chitosan-tetracycline nanoparticles, which allows the sequential release of tetracycline and lovastatin to effectively control local infection and promote bone regeneration in periodontitis. The size and microstructure of nanoparticles were examined by transmission electron microscopy, Nanoparticle Size Analyzer, and Fourier transform infrared spectroscopy. The release of tetracycline and lovastatin was quantified using a UV-Vis spectrophotometer. Furthermore, the cytotoxic effect and alkaline phosphatase activity of the nanoparticles in osteoblast cell cultures as well as antibacterial activity against periodontal pathogens were investigated. Finally, the bone regeneration potential of PLGA nanoparticles in three-walled defects in beagle dogs was investigated. The results indicated that PLGA-lovastatin-chitosan-tetracycline nanoparticles showed good biocompatibility, antibacterial activity, and increased alkaline phosphatase activity. The volumetric analysis from micro-CT revealed significantly increased new bone formation in defects filled with nanoparticles in dogs. This novel local delivery device might be useful as an adjunctive treatment in periodontal regenerative therapy. Keywords: lovastatin, tetracycline, chitosan, poly(d,l-lactide-co-glycolide acid), periodontal regeneration